Pembangunan Perangkat Lunak ITMG (Integrated Touristic Map Generator) - Afnarius, Surya (JIK: Jurnal Ilmu Komputer, 2008)
One study to generate SVG Touristic Map using shapefile had been done. The study solved the problem cost of e-government implementation using Internet-GIS in tourism service. This reports the results of an effort to develop a software called Ã¢â‚¬Å“ITMGÃ¢â‚¬Â. To develop software, the waterfall methodology was used in this study. The study used Visual Basic, Access, MapObjects and ASP. The ITMG was tested using Padang Map.The results showed that the ITMG fulfills the user requirements in tourism service.Keywords: e-Governmen, Internet, GIS, Map - Shapefile